MODEL PEMBELAJARAN PAI DALAM MEMBENTUK KEPRIBADIAN ISLAMI SISWA DI SMK DR WAHIDIN SAWAHAN NGANJUK - Moch. Sya’roni Hasan; Nikmawati Nikmawati (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2020)
The background of this research is the concern about the moral degradation of the nation's future generations. This condition occurs due to various factors, both internal and external factors. Therefore schools as institutions of education, especially teachers as educators must have a learning model that can form Islamic character and personality for students. The focus of this research is how the PAI learning model in Vocational Dr. Wahidin Sawahan Nganjuk, How is the personality of Islamic students in Vocational Dr. Wahidin Sawahan Nganjuk. This type of research uses a qualitative approach. Data collection methods: observation, interview and documentation. The data analysis technique uses the interactive model of Miles and Huberman which includes data reduction, data presentation and drawing conclusions. To check the validity of the data used research extension, observation persistence and triangulation. With the inculcation of Islamic personality early on in students it will form a good personality in accordance with Islamic law in someone in the future. The hope is that with the PAI learning model in helping the personality of students at the Vocational School Dr. Wahidin Sawahan Nganjuk can be used as a reference to improve learning and a good personality going forward.